Respon Siswa terhadap Penggunaan Media Film Dokumenter Berbasis Situs Sejarah Lokal - Ira Miyarni Sustianingsih; Risa Marta Yati (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
The purpose of this study was to determine students' responses to history learning using documentary film media based on local historical sites at SMKN 1 Lubuklinggau. This research method is included in development research using a 4-D research model which has been modified into 3-D including the Definition stage, the Planning stage, and the Development stage. The data collection technique used in this study was to provide a response questionnaire after learning using documentary film media based on local historical sites was completed, with a total of 18 questions. Furthermore, the data collection technique used is in the form of a Likert scale. The results of the study based on the calculation of the results of the response questionnaire that were filled in by the students showed that the average score of student responses was 75.6% in the good category. The conclusion of this study as a whole the students gave positive responses, besides that the documentary film media based on local historical sites was quite liked when it was used in the learning process. Keywords: Development, Documentary Film Media, Local History